Electrification of residential space heating considering coincidental weather events and building thermal inertia: A system-wide planning analysis. (15th May 2017) - Heinen, Steve; Turner, William; Cradden, Lucy; McDermott, Frank; O'Malley, Mark
Abstract: The increasing deployment of variable renewables and parallel residential space heat electrification using heat pumps poses two significant challenges for electricity systems: First, coincidence of certain weather events can stress the power system due to the increasing weather-dependence on both supply and demand side; Secondly, increased net load demand requires large capacity expansion unless heat and electricity can be partially decoupled. This paper proposes a planning methodology to explore these challenges by integrating a 'Resistance-Capacitance' representation of building thermodynamics into an integrated planning model. This enables analysis of coincidental weather effects which drive system adequacy and of the potential to utilise building thermal inertia to pre-heat the building and effectively store electricity in the form of heat according to system conditions. The model was tested with a case study for the Irish energy system in 2030. It was found that different weather patterns considerably influence investment and planning choices. Also, coincidental effects of different weather variables – in this case, low temperatures and low wind speed - define the most critical situations in terms of adequacy. By utilising building thermal inertia, total system costs of residential heat electrification can be reduced to the level of the benchmark technology, gas boilers. Highlights: System with high wind penetration is modelled to analyse space heating electrification. Building thermodynamics are explicitly captured in the system-wide planning model. System adequacy is stretched when low wind and low temperature weather events coincide. Preheating building thermal mass makes space heat electrification cost-effective. Resulting system-wide benefits justify the energy increase from pre-heating.